Analysis of the Basic Sector and the Contribution of Economic Sectors to Economic Growth in the City of Jayapura - Tame, Yusuf Serang; Marlissa, Elsyan R; Ngutra, Risky Novan (Penerbit Goodwood, 2024)
Purpose: Economic development is a structured effort to manage resources in order to improve community welfare. This study aims to: (1) analyze the contribution trends of each economic sector to Jayapura City's GRDP from 2019 to 2023; (2) identify the sector with the highest contribution during this period; and (3) determine which sectors serve as base (leading) sectors using Location Quotient (LQ) analysis. Research methodology: The study applies descriptive analysis and the LQ method by comparing the share of each economic sector in Jayapura City to that in Papua Province. Secondary data from 2019 to 2023 was analyzed to assess sectoral performance and identify strategic sectors for regional development. Results: The findings show that the top contributing sectors are Construction (24.39%), Wholesale and Retail Trade including Motor Vehicle and Motorcycle Repair (17.97%), and Government Administration, Defense, and Mandatory Social Security (10.87%). These three sectors together contribute more than 50% to Jayapura’s total GRDP. Sectors with LQ > 1—such as Construction, Financial Services, and Information and Communication—are considered base sectors, indicating they produce beyond local needs and drive economic growth. Conclusion: Jayapura City’s economic structure is dominated by a few key sectors that play a central role in development planning and economic resilience. Limitation: This research is limited to Jayapura City and does not analyze comparative or qualitative dimensions, such as employment quality or policy impact. Contribution: The study supports regional planning by providing an empirical foundation to prioritize investments and policy in high-performing and base sectors.